First report of a 16SrIII-X phytoplasma associated with Lactuca sativa witches’-broom in Argentina - Fernandez, Franco Daniel; Carloni, Edgardo José; Alessio, Florencia Ivette; Bongiorno, Vanina Aylén; Conci, Luis Rogelio (Wiley, 2025)
During the summer of 2022, symptoms of witches’-broom, flowering malformation and redness were observed in lettuce plants (Lactuca sativa) in fields in Cordoba Province, Argentina (Fig. 1a). In the same fields, garlic (Allium sativum) plants exhibiting symptoms of phyllody (Fig. 1b-c) were also observed. To confirm the presence of phytoplasma, leaf samples from two diseased lettuce and three garlic plants were collected. As negative controls, leaf samples from symptomless plants (one lettuce and two garlic) were collected. Garlic decline phytoplasma (subgroup 16SrIII-J) was reported previously in association with Garlic decline disease in Argentina (Conci et al., 1998). However, this is the first time that symptoms of phyllody in garlic associated with this phytoplasma have been reported. To our knowledge, this is the first report of phytoplasmas from subgroup 16SrIII-X affecting lettuce in Argentina and worldwide. Previous work reported the presence of phytoplasmas from subgroup 16SrIII-X affecting different species of weeds in the same region (Galdeano et al., 2013; Fernández et al., 2020) which may suggest the presence of a common insect vector with polyphagous feeding behaviour.